2022
DOI: 10.1097/aog.0000000000004971
|View full text |Cite
|
Sign up to set email alerts
|

Allostatic Load and Adverse Pregnancy Outcomes

Abstract: OBJECTIVE:To assess the association between allostatic load, as an estimate of chronic stress, and adverse pregnancy outcomes. METHODS:This was a secondary analysis of nuMoM2b (Nulliparous Pregnancy Outcomes Study: Monitoring Mothers-to-Be), a prospective observational cohort study. Our primary exposure was dichotomous high allostatic load in the first trimester, defined as 4 or more of 12 biomarkers in the "worst" quartile. The primary outcome was a composite adverse pregnancy outcome: hypertensive disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Studies have highlighted that AL may be a key biological mediator of the minority stress effects on racial disparities in health and mortality. 20,23,24,76,85,86 Notably, high allostatic load is associated with both mental and physical health outcomes 1 and with greater all-cause mortality, 19 with additive contribution of AL to exposomic burden in explaining mortality. 23,76 Our results in a young developing population therefore concur with the existing literature in older populations regarding the links between environment and AL and between AL and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have highlighted that AL may be a key biological mediator of the minority stress effects on racial disparities in health and mortality. 20,23,24,76,85,86 Notably, high allostatic load is associated with both mental and physical health outcomes 1 and with greater all-cause mortality, 19 with additive contribution of AL to exposomic burden in explaining mortality. 23,76 Our results in a young developing population therefore concur with the existing literature in older populations regarding the links between environment and AL and between AL and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The total allostatic load score was summed for an allostatic load index ranging from 0 to 12. Low allostatic load was reported as an index of less than 4, and high allostatic load was an index of 4 or more because previous studies found this threshold to be discriminatory 16,17 . Allostatic load was included in analysis as a dichotomous variable (high versus low).…”
Section: Methodsmentioning
confidence: 99%
“…Low allostatic load was reported as an index of less than 4, and high allostatic load was an index of 4 or more because previous studies found this threshold to be discriminatory. 16,17 Allostatic load was included in analysis as a dichotomous variable (high versus low). Clinically relevant thresholds for some variables, particularly in pregnancy, are unavailable.…”
Section: Allostatic Loadmentioning
confidence: 99%
“…It has been associated with adverse pregnancy outcomes such as preterm birth, stillbirth, newborns small for gestational age, and hypertensive disorders of pregnancy. [56][57][58] Allostatic load in relation to stereotype threat, along with other forms of systemic racism, may explain some of the reproductive and pregnancy disparities in Black individuals.…”
Section: : Partus Sequitur Ventrem and The Intersection Between Race ...mentioning
confidence: 99%